New methodology of TMB assessment from tissue and liquid biopsy in NSCLC - Křížová, Ľudmila; Šafaříková, Markéta; Kalousová, Marta; Pfeiferová, Lucie; Kuběna, Aleš Antonín; Vočka, Michal; Ulrych, Jan; Franková, Věra; Petruželka, Luboš; Zima, Tomáš; Feltl, David (PLoS One, 2022)
Immunotherapy has dramatically influenced and changed therapeutical approach in non-small cell lung cancer (NSCLC) in recent five years. Even though we can reach long-term response to this treatment in approximately 20% of patients with NSCLC, we are still not able to identify this cohort of patients based on predictive biomarkers. In our study we have focused on tumor mutation burden (TMB), one of the potential biomarkers which could predict effectiveness of check-point inhibitors, but has several limitations, especially in multiple approaches to TMB quantification and ununiform threshold. We determined the value of TMB in tumor tissue (tTMB) and blood (bTMB) in 20 patients with early stage NSCLC using original custom gene panel LMB_TMB1. We evaluated various possibilities of TMB calculation and concluded that TMB should be counted from both somatic non-synonymous and synonymous mutations. Considering various factors, we established cut-offs of tTMB in/excluding HLA genes as ≥22 mut/Mb and 12 mut/Mb respectively, and cut-offs of bTMB were defined as ≥21 mut/Mb and ≥5 mut/Mb, respectively. We also observed trend in correlation of somatic mutations in HLA genes with overall survival of patients.
Keywords: Biomarkers, Tumor; Liquid Biopsy; nádory plic; nemalobuněčný karcinom plic; nádorové biomarkery; mutace; Lung Neoplasms; Humans; Mutation; lidé; tekutá biopsie; Carcinoma, Non-Small-Cell Lung